Catalase-like nanozymes combined with hydrogel to facilitate wound healing by improving the microenvironment of diabetic ulcers. (January 2023) - Wang, Songqi; Zhang, Yulin; Sun, Fengying; Xi, Kaiyan; Sun, Zhenwei; Zheng, Xiaoyue; Guo, Fengzhen; Zhong, Hanlin; Yang, Mengmeng; Shao, Yuting; Huang, Bin; Dong, Ming; et al.
Graphical abstract: We prepared multifunctional nanoparticles (EGAP) with antibacterial, antioxidant, anti-inflammatory, oxygen supply, pro-angiogenic and good biocompatibility, then encapsulated them in temperature-sensitive hydrogels and applied them to chronic wounds, and finally improved the complex local microenvironment of diabetic wounds by local injection to accelerate wound healing. Highlights: Chronic wound ulcers is a serious complication of diabetes. The microenvironment of diabetic wounds is sophisticated and detrimental to tissue restoration. Catalase-like nanozymes (GAP) improve the hypoxic environment of wounds. Multifunctional nanomedicines (EGAP@HG) can reverse the unfavorable microenvironment and promote ulcer healing. Abstract: Diabetic wounds have a complex microenvironment, due to local hypoxia, bacterial infection, and the accumulation of reactive oxygen species. Multiple adverse factors contribute to the non-healing state. Without effective treatment, diabetic wounds can lead to serious systemic complications. The current clinical treatments of enhanced glycemic control and anti-infection are unable to meet the needs of diabetic wound management. Here, we constructed a nanoparticle with catalase-like functionality (EGAP) and encapsulated it in a thermosensitive hydrogel to yield a versatile hydrogel formulation (EGAP@HG). The drug can form a protective physical barrier over the wound and create a moist environment. First, the EGAP converts H2 O2 to O2 at the wound site, thereby alleviating local hypoxia. Then, the released EGF can promote the proliferation of epidermal cells. Furthermore, the gallic acid released from the outer layer of EGAP can exert anti-inflammatory and antioxidant effects. Finally, the silver ions released from the inner templates (APs) can kill bacteria. In vivo and in vitro experiments have shown that our treatment system can promote wound healing from multiple perspectives. This strategy by improving the local microenvironment of diabetic wounds provides a new theoretical basis and practical directions for chronic diabetic wound repair.